2020
DOI: 10.3390/e22070740
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Wear and Corrosion Behavior of AlCoCrFeNi High-Entropy Alloy Coatings Synthesized by Atmospheric Plasma Spraying

Abstract: High-entropy alloy coatings (HEAC) exhibit good frictional wear and corrosion resistances, which are of importance for structure materials. In this study, the microstructure, surface morphology, hardness, frictional wear and corrosion resistance of an AlCoCrFeNi high-entropy alloy coating synthesized by atmospheric plasma spraying (APS) were investigated. The frictional wear and corrosion resistance of the coating are simultaneously improved with an increase of the power of APS. The influence of the AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Higher cooling rate results in a more refined dendritic structure, resulting in a smoother surface. Finer microstructures offer improved hardness, which in turn offer higher wear resistance [65][66][67]. It may be observed that in general, the wear resistance of the HPSC decreases with increasing load and/temperature combination due to accelerated conditions (which is as expected).…”
Section: Wear Behaviorsupporting
confidence: 57%
“…Higher cooling rate results in a more refined dendritic structure, resulting in a smoother surface. Finer microstructures offer improved hardness, which in turn offer higher wear resistance [65][66][67]. It may be observed that in general, the wear resistance of the HPSC decreases with increasing load and/temperature combination due to accelerated conditions (which is as expected).…”
Section: Wear Behaviorsupporting
confidence: 57%
“…With increasing current density, extensive delamination and coating failure occurred. In contrast to previous investigations on APS coatings of the same composition, there is no passivation for the investigated test conditions [18]. The average characteristic values for both corrosion types are summarized in Table 5.…”
Section: Corrosion Behaviormentioning
confidence: 79%
“…Thermally sprayed AlCrFeCoNi coatings produced by atmospheric plasma spraying (APS) were investigated by Mu et al in 3.5 wt.% NaCl electrolyte, and were revealed to have high corrosion resistance. The formation of a passive film, which is comprised of Cr and Fe oxides, could be proven despite the relatively heterogeneous condition due to feedstock oxidation during thermal spraying [18]. Investigations of laser cladded coatings in 0.6 M NaCl electrolyte also clearly showed passivation and an improved corrosion resistance in comparison to the stainless steel AISI 304L (EN 1.4306) [19].…”
Section: Introductionmentioning
confidence: 95%
“…Numerous studies suggest that these metallic alloys have the potential to mitigate wear and corrosion compared to traditional alloys. [1][2][3] HEAs are characterized by their multicomponent compositions (five or more elements) DOI: 10.1002/adem.202101713 High entropy alloys (HEAs) represent a new class of advanced metallic alloys that exhibit unique structural features and promising properties. The potential benefit of HEAs, in conjunction with established thermal spray manufacturing technologies, can provide a practical approach to mitigate wear and corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest that these metallic alloys have the potential to mitigate wear and corrosion compared to traditional alloys. [ 1–3 ] HEAs are characterized by their multicomponent compositions (five or more elements) mixed in equimolar or close to equimolar concentrations, enabling them to form a single‐phase solid solution. [ 4 ] However, the formation of intermetallics together with solid solution phases was also reported for the HEAs.…”
Section: Introductionmentioning
confidence: 99%